Murder by Usury and Organised Denial: A critical realist perspective on the liberating paradigm shift from psychopathic dominance towards human civilisation - Priels, Koenraad (Journal of Critical Realism in Socio-Economics (JOCRISE), 2022)
The discipline of sociology is in a deplorable condition as it has a pervasive blind spot for the social dynamics of compound interest on credit, resulting in a systematic collective incompetence to bring well-informed structural solutions to the socio-ecological crises that human societies are facing everywhere around the world.